Effects of high-flow nasal cannula in patients with mild to moderate hypercapnia: a prospective observational study - Nam, Kyung Hun; Kang, Hyung Koo; Lee, Sung-Soon; Park, So-Hee; Kang, Sung Wook; Hwang, Jea Jun; Park, So Young; Kim, Won Young; Suh, Hee Jung; Kim, Eun Young; Seo, Ga Jin; Koh, Younsuck; et al. (Acute and critical care, 2021)
Background: Evidence for using high-flow nasal cannula (HFNC) in hypercapnia is still limited. Most of the clinical studies had been conducted retrospectively, and there had been conflicting reports for the effects of HFNC on hypercapnia correction in prospective studies. Therefore, more evidence is needed to understand the effect of the HFNC in hypercapnia.Methods: We conducted a multicenter prospective observational study after applying HFNC to 45 hospitalized subjects who had moderate hypercapnia (arterial partial pressure of carbon dioxide [PaCO2], 43–70 mm Hg) without severe respiratory acidosis (pH <7.30). The primary outcome was a change in PaCO2 level in the first 24 hours of HFNC use. The secondary outcomes were changes in other parameters of arterial blood gas analysis, changes in respiration rates, and clinical outcomes.Results: There was a significant decrease in PaCO2 in the first hour of HFNC application (-3.80 mm Hg; 95% confidence interval, -6.35 to -1.24; P<0.001). Reduction of PaCO2 was more prominent in subjects who did not have underlying obstructive lung disease. There was a correction in pH, but no significant changes in respiratory rate, bicarbonate, and arterial partial pressure of oxygen/fraction of inspired oxygen ratio. Mechanical ventilation was not required for 93.3% (42/45) of our study population.Conclusions: We suggest that HFNC could be a safe alternative for oxygen delivery in hypercapnia patients who do not need immediate mechanical ventilation. With HFNC oxygenation, correction of hypercapnia could be expected, especially in patients who do not have obstructive lung diseases.